Advances Achieved by Ionic-Liquid-Based Materials as Alternative Supports and Purification Platforms for Proteins and Enzymes - Rui M. F. Bento; Catarina A. S. Almeida; Márcia C. Neves; Ana P. M. Tavares; Mara G. Freire (Nanomaterials, 2021)
Ionic liquids (ILs) have been applied in several fields in which enzymes and proteins play a noteworthy role, for instance in biorefinery, biotechnology, and pharmaceutical sciences, among others. Despite their use as solvents and co-solvents, their combination with materials for protein- and enzyme-based applications has raised significant attention in the past few years. Among them, significant advances were brought by supported ionic liquids (SILs), in which ILs are introduced to modify the surface and properties of materials, e.g., as ligands when covalently bond or when physiosorbed. SILs have been mainly investigated as alternative supports for enzymes in biocatalysis and as new supports in preparative liquid chromatography for the purification of high-value proteins and enzymes. In this manuscript, we provide an overview on the most relevant advances by using SILs as supports for enzymes and as purification platforms for a variety of proteins and enzymes. The interaction mechanisms occurring between proteins and SILs/ILs are highlighted, allowing the design of efficient processes involving SILs. The work developed is discussed in light of the respective development phase and innovation level of the applied technologies. Advantages and disadvantages are identified, as well as the missing links to pave their use in relevant applications.